2020
DOI: 10.17219/acem/111809
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the use of lycopene to prevent infertility due to acute oxidative ovarian damage caused by a single high dose of methotrexate

Abstract: Background. Methotrexate (MTX) is an antineoplastic agent, which increases the level of reactive oxygen species (ROS) and decreases the level of antioxidants. Lycopene, is a potent antioxidant, which is used because of its protective effect against tissue damage.Objectives. The aim of this study was to determine the effect of lycopene on ovarian MTX-induced injury in rats.Material and methods. Rats (n = 36) were randomly divided into 3 equal groups: a group with MTX only (MG, n = 12), a group with lycopene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, apoptosis and DNA damage were not evaluated in this study. In previous studies, protective effects of alpha lipoic acid and lycopene on MTX-induced ovarian damage have also been demonstrated (37,38). In another study, Chen et al (39) studied the ovaries of aging rats and suggested that RES increases the follicle reserve in this process and prevents atresia.…”
Section: Discussionmentioning
confidence: 94%
“…However, apoptosis and DNA damage were not evaluated in this study. In previous studies, protective effects of alpha lipoic acid and lycopene on MTX-induced ovarian damage have also been demonstrated (37,38). In another study, Chen et al (39) studied the ovaries of aging rats and suggested that RES increases the follicle reserve in this process and prevents atresia.…”
Section: Discussionmentioning
confidence: 94%
“…For this reason, MDA may cause exacerbation of LPO damage and further destruction (Suleyman and Ozcicek, 2019). In the studies conducted previously, it was observed that antioxidant levels decreased in ovarian tissue where MDA was increased (Turkler et al, 2020). Another study remarked that cyclophosphamide caused an increment in MDA levels and a reduction in antioxidants and had a toxic effect on the ovaries (Saleh and Mansour, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Dietary supplementation with lycopene at 20 mg per day for 3 months prior to the scheduled in vitro fertilization (IVF) treatment increased the arachidonic acid to docosahexaenoic acid ratio in the seminal fluid and resulted in 7 natural pregnancies in addition to 15 pregnancies following the IVF procedure [ 51 ]. In methotrexate-induced ovarian damage, pretreatment with lycopene at 5 mg/kg body weight for 5 days prevented infertility and has shown to mediate increased GSH activity as well as decreased MDA and myeloperoxidase concentrations [ 211 ]. These findings suggest that lycopene alleviates imbalances in polyunsaturated fatty acids and can serve as a preventive agent against infertility.…”
Section: Biological Activities Of Lycopenementioning
confidence: 99%